2005
DOI: 10.1111/j.1075-122x.2005.21641.x
|View full text |Cite
|
Sign up to set email alerts
|

How Mammillary Fistulas Should Be Managed

Abstract: Mammillary fistulas are uncommon, but when they occur they cause prolonged morbidity. The etiology and management strategies are less well established. The purpose of this study is to evaluate the etiologic factors and assess the results of surgical treatment. It is a retrospective study of all patients treated for mammillary fistula from 1990 to 2001. The clinical data, including complications of surgical treatment, were collected from medical records. Fistulas were segregated into simple and complex fistulas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 6 publications
0
24
0
5
Order By: Relevance
“…Gollapalli et al 5 found that smokers are six times more likely to develop primary abscess when compared to non-smokers (OR of 6.15, 95% CI 2.65–14.29). Spontaneous drainage onto the border of the areola signifies the development of a fistulous tract 2 3 6. Other authors have demonstrated inconsistency with this theory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gollapalli et al 5 found that smokers are six times more likely to develop primary abscess when compared to non-smokers (OR of 6.15, 95% CI 2.65–14.29). Spontaneous drainage onto the border of the areola signifies the development of a fistulous tract 2 3 6. Other authors have demonstrated inconsistency with this theory.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have demonstrated inconsistency with this theory. Hanavadi et al 6 concluded that periductal mastitis is more commonly the culprit, as they were unable to consistently identify a keratin plug or duct ectasia. Likewise, in a study of 52 fistulas, Lambert et al 7 drew similar conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, few authors have focused on the multiply recurrent form of this disease; these patients who have already undergone multiple surgeries with failure are a highly selected group. The need to excised dilated lactiferous terminals is no longer debated nowadays but the techniques vary [10][11][12][13]. In a series of 204 periareolar abscesses, Lesanka Versluijs-Ossewaarde reported a 79% recurrence rate if surgical excision did not included the lactiferous ducts versus 28% when the terminal lactiferous ducts were excised [14].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the lack of awareness of the treating physicians, these patients are subjected to undue stress and radical procedures which are unnecessary most of the times. Till date, the only definitive treatment for this condition is only surgical (microdochectomy, fistulectomy, and major mammary duct excision) [7][8][9]. Hence, it becomes surgically relevant to study the disease process, in order to gain a good knowledge of these benign breast diseases, which is in turn necessary to alleviate the fear of cancer and appropriately treat the disease.…”
Section: Introductionmentioning
confidence: 99%